Heterotopic pregnancy (cervical & tubal pregnancy) - Daghstani, Mazin H.; Hassan, Albagir M. Ahmed (Gezira Journal of Health Sciences, 2019)
Heterotopic pregnancy is the presence of intrauterine pregnancy (living or deadsingle or multiple) and extra-uterine pregnancy which located in the fallopian tubes, ovary, uterine corner, cervix or peritoneal cavity. This condition is very rare (1:30 000 pregnancies). With the development and accessibility of assisted reproductive techniques, the incidence of heterotopic pregnancies increased to 1:100 of pregnancies. The aim of this report is to present a case of early recognized double ectopic pregnancy tubal and cervical pregnancy. The case is a 30 years old Saudi lady 6 weeks gestation in her 3rd pregnancy the first was twin pregnancy delivered by spontaneous vaginal delivery and the 2nd is term singleton pregnancy delivered also by spontaneous vaginal delivery.  The patient admitted because of vaginal bleeding and abdominal pain lasting for 48 hours diagnosed as ruptured left tubal pregnancy and underwent emergency laparotomy in which left salpingectomy was done and the other tube and both ovaries were normal. Patient discharge in a good condition 3 days after the surgery. Patient seen in her follow up visit 4 days after discharge serum βhCG was still high ultrasound reviled a viable pregnancy in the posterior lower part of the uterus at the junction with cervix. Laparoscopic successfully guided feticide is donefollowed by IM injection of Methotrexate. Patient had a spontaneous pregnancy which was uncomplicated till she had a spontaneous delivery without complications 1 year later.